2008
DOI: 10.1017/s1740925x09000015
|View full text |Cite
|
Sign up to set email alerts
|

NG2 cells generate oligodendrocytes and gray matter astrocytes in the spinal cord

Abstract: NG2 cells represent a unique glial cell population that is distributed widely throughout the developing and adult CNS and is distinct from astrocytes, mature oligodendrocytes and microglia. The ability of NG2 cells to differentiate into myelinating oligodendrocytes has been documented in vivo and in vitro. We reported recently that NG2 cells in the forebrain differentiate into myelinating oligodendrocytes but into a subpopulation of protoplasmic astrocytes (Zhu et al., 2008). However, the in vivo fate of NG2 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
132
4
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(143 citation statements)
references
References 36 publications
6
132
4
1
Order By: Relevance
“…with the preserved tissue organization) the paracrine signals proved to be potent to force the as troglial commitment of OPCs. There are also reports describing a similar in vivo effect, found in different CNS regions [33,56]. The observation coming from our study concerning the promotion of astroglial differentiation in cocultures with hippocampal and spinal cord sli ces are in agreement with the reports about the glial scar formation in injuries occurring to the brain and spinal cord.…”
Section: Discussionsupporting
confidence: 92%
“…with the preserved tissue organization) the paracrine signals proved to be potent to force the as troglial commitment of OPCs. There are also reports describing a similar in vivo effect, found in different CNS regions [33,56]. The observation coming from our study concerning the promotion of astroglial differentiation in cocultures with hippocampal and spinal cord sli ces are in agreement with the reports about the glial scar formation in injuries occurring to the brain and spinal cord.…”
Section: Discussionsupporting
confidence: 92%
“…4C,J). A recent study showed that NG2 positive cells can also differentiate into astrocytes in the spinal cord gray matter (Zhu et al, 2008). Therefore, we also used another OPC marker PDGFRa which has a defined function in OL development (Richardson et al, 1988), and obtained very similar results (Fig.…”
Section: Influence Of Olig Overexpression On Ol Differentiationmentioning
confidence: 52%
“…In the G93A mSOD1 transgenic mouse, activation of astrocytes occurs concomitantly with a decrease in motor neurons [75,82,83]. Although astrocyte numbers increase with disease progression, astrocytes do not proliferate like microglia, but may be derived from ependymal cells lining the central canal of the spinal cord or oligodendrocyte precursor cells [24,[84][85][86][87][88].…”
Section: Astrogliamentioning
confidence: 99%